The Development of Da'wah Through Tabligh and the Development of Da'wah Ideas in Indonesia - Gantira, Erlan (Asyahid Journal of Islamic and Quranic Studies (AJIQS), 2023)
Now, tabligh preaching through oral and written lectures can be combined into one medium, namely digital media, so the preachers' abilities must be even more capable because media can now become a convergent media, namely a combination of written and video/film media. The condition of tabligh preaching in the midst of increasing political behavior brings challenges and notes for preachers to choose neutral ideas or lecture material, because basically Islam is a religion of Rahmatan lil allamin, always providing peace and tranquility for all creatures and their lives. Da'wah ideas and materials do not have to be titles and preaching materials but also other ideas that are easily accepted in society, enter into their social behavior and social strata, so that they become an "injection" of goodness for the people. The results of the research show that the idea of ​​da'wah using the tabligh method in Indonesia is still a popular way of da'wah. However, often when some ulama in Indonesia deliver preaching material in a tabligh forum that deals with government performance or criticism of the authorities, they are considered "left" ulama. So tabligh da'wah often intersects with the democratization of da'wah itself. In the current era of democratization of da'wah, it is often collided with group differences and issues of anti-nationalism and diversity. The dissolution of recitation forums because the preacher is the resource person often occurs. If in the past the prohibition on preaching was carried out by elements in power, now it is carried out by elements of mass organizations which are basically of the same religion, fellow Muslims. If a preacher has preaching content that lacks data and references, he will receive direct criticism and even ridicule from netizens. Keywords: da'wah, democratic, internet, critical, netizen.   Abstrak Sekarang, dakwah tabligh melalui ceramah lisan dan tulisan bisa disatukan menjadi satu media, yaitu media digital, sehingga kemampuan mubaligh harus lebih mumpuni lagi karena media sekarang dapat menjadi media convergen yaitu perpaduan antara media tulisan dan video/film. Kondisi berdakwah tabligh di tengah perilaku politik yang meningkat membawa tantangan dan catatan bagi da’i untuk memilih Ide ataupun materi ceramah yang netral, karena pada dasarnya Islam adalah agama Rahmatan lil allamin, selalu memberikan kedamaian dan ketengan untuk seluruh makhluk dan kehidupannya. Ide dan materi dakwah tidak harus berupa judul dan materi dakwah namun juga ide-ide lainnya yang mudah diterima di Masyarakat, masuk ke dalam perilaku sosial dan strata sosial mereka, sehingga menjadi “suntikan” kebaikan bagi umat. Hasil peneleitian menunjukkan bahwa ide dakwah dengan cara tabligh di Indonesia masih menjadi cara dakwah yang populer. Namun seringkali beberapa ulama di Indonesia ketika menyampaikan materi dakwah dalam sebuah forum tabligh yang bersinggungan dengan kinerja pemerintah atau kritikan-kritikan kepada penguasa akan dianggap sebagai ulama yang beraliran “kiri”. Sehingga dakwah tabligh seringkali bersinggungan dengan demokratisasi dakwah itu sendiri. Di saat ini era demokratisasi dakwah sering dibenturkan dengan perbedaan golongan dan issue anti nasionalisme dan kebhinekaan. Pembubaran forum-forum pengajian karena da’i yang menjadi narasumber sering terjadi. Apabila dahulu larangan dakwah dilakukan oleh unsur penguasa maka sekarang ini dilakukan oleh unsur organisasi masa yang dasarnya se-agama, sesama muslim. Seorang mubaligh bila mempunyai konten dakwah yang minim data dan referensi akan mendapatkan kritikan langsung bahkan cemoohan dengan umat netizen. Kata kunci: dakwah, demokratis, internet, kritis, netizen